PHYSICOCHEMICAL AND MICROBIOLOGICAL RESULTS FROM HOT MINERAL WATER IN THE VILLAGE OF VARVARA, DISTRICT OF PAZARDZHIK, BULGARIA - IGNATOV, IGNAT; VALCHEVA, NEDYALKA; POPOVA, TEODORA P.; NESHEV, NIKOLAI; HUETHER, FABIO; IGNATOV, ALEXANDER I. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
There are 225 mineral springs in Bulgaria, and out of them, 148 are in southern Bulgaria and 77 in northern Bulgaria. The region with mineral water “Varvara” is located in Rhodope mountains, Pazardzhik region, Bulgaria. Physicochemical and microbiological research of two springs from the village of Varvara is presented in the article. The springs are “Drilling No. 3 - Varvara” and “Drilling No. 5 – Varvara”. The physicochemical research of mineral waters showed that it is characterized as hydrothermal, mineralized, hydrocarbon-sulphate, sodium, silicon-rich and fluoride waters. The hyperthermal mineral spring “Drilling No. 3 – Varvara” is with t=79.9°С. The hyperthermal mineral spring “Drilling No. 5 – Varvara” is with t=83.7°С. The presence of single spores of species of genus Bacillus (Bacillus subtilis, Bacillus licheniformis), phylum Bacillota were found in the tested mineral waters. B. subtilis is a Gram-positive bacterium that forms heat-resistant spores. B. licheniformis is a Gram-positive, mesophilic bacterium and its optimal growth temperature is around 50°С. B. licheniformis can survive at higher temperatures. Geobacillus stearothermophilus also was registered in the tested mineral waters. It is a rod-shaped, Gram-positive bacterium, a member of the phylum Bacillota. The results show that the waters from both examined sources in Varvara are useful for human health according to their physicochemical composition. The content of silicon and calcium is a prerequisite for their application in strengthening the musculoskeletal system. The rich fluoride content allows their controlled use for reduction in dental caries. The waters from “Drilling No. 3 - Varvara” and “Drilling No. 5 - Varvara” did not show any sanitary- chemical and microbiological signs of contamination. This reveals opportunities for balneological therapy and tourism in this region. Bottling these waters would allow for their wider use.